Live coral predation by fish in Tayrona Nature National Park, Colombian Caribbean - Reyes-Nivia, María Catalina (2004)
Live coral predation by fish was evaluated in two bays of the Tayrona National Natural Park (Colombia), as a possible biological agent causing coral mortality. Visual censuses were used to identify the most important predator. Predation incidence was determined by examining all colonies present in permanent belt transects (20 x 2 m) in two reef environments (one dominated by Colpophyllia natans and the other one by Montastraea faveolata), for two climatic seasons (rainy and dry seasons). The parrotfish Sparisoma viride was the most important predator due to its biting frequency and bite size. S. viride adults of the initial and terminal phases, removed live tissue and part of the calcareous matrix of M. faveolata, M. annularis, Porites astreoides and C. natans, of which, the last one lost a major amount of tissue per area (3.51 cm2) and volume (3.22 cm3) per bite. A negative exponential tendency (r2=0.94), between coral density and volume removed was found, indicating that the coral density determines the bite’s damage. There is no clear relationship between predation incidence and climatic seasons at the sites studied. At Chengue and Gayraca bays, live coral predation is one of the factors contributing to coral tissue loss and could have important consequences on the dynamic of these reefs